Textbook of medical parasitology - Paniker, C. K. Jayaram; Ghosh, Sougata, M.D. (N/A Jaypee Brothers Medical Pub, 2013)
The seventh edition of this textbook has been fully revised to provide undergraduate students with the most up to date information in the field of parasitology. Beginning with a general introduction to the subject, each of the following chapters presents students with essential information on key parasites and parasitic diseases. The final chapter is dedicated to diagnostic methods and has been completely updated to include the latest technological developments. Highly illustrated, with many new or updated figures and photographs, each chapter includes 'key points' boxes, as well as review questions to assist with preparation for exams. Key points * Fully revised, new edition presenting latest developments in parasitology * Covers all key parasites and parasitic diseases * Review questions for each chapter * Previous edition published in 2007.